A Possible Interpretation - Gradvohl, Edina (Acta Classica Universitatis Scientiarum Debreceniensis, 2024)
This paper attempts to interpret a gem of uncertain date and questionable origin, with Greek inscriptions and letters, and which is in the National Library of France (BNF inv.58.2220). Based on previous interpretations and the surviving impression and description of a pendant which is very similar to it in material and subject, it can be shown that the gem is original, and Christian, based on the depictions on it and the clearly legible word "ΧΡΙCΤΟC".